Draft Third Five Year Plan (1961-66) Part I Jammu and Kashmir State - Planning Commission (Planning Commission, 1960)
The main objectives of the Country's Third Five Year Plan were suggested by the National Development Council as being to (I) secure a rise in national income of at least 5 per cent. per annum, the pattern of investment being designed also to sustain this rate of growth during subsequent plan periods; (ii) achieve self-sufficiency in food grains, and increase agricultural production ; (iii) establish basic industries ; (iv) ensure a substantial expansion in employment opportunities and (v) bring about a reduction of inequalities in income and wealth and a more even distribution of economic power.
Jammu and Kashmir State